An exploration of Doctor's perceptions and the provision of Palliative Care at a Private Hospital in Gauteng, South Africa. - Booth, Elizabeth Cecile (Department of Medicine, 2021)
Introduction: Palliative care is a core component of comprehensive health care across a person's life span. South Africa is currently in the process of integrating palliative care into all levels of the health care system. Doctors play a vital role in providing these services, but misconceptions about palliative care and who should be providing it, may prevent these services from being offered. Aim: The aim of this study was to discover doctor's perceptions and the current provision of palliative care in a private hospital. Objectives: The objectives of the study were: (1) to explore doctors' experiences of pain and symptom management in palliative care; (2) to explore doctors' perceptions of palliative care, goals of care and teamwork in palliative care; and (3) to explore the doctors' provision of palliative care at the hospital. Methodology: This was a qualitative study using a grounded theory approach. Semi-structured interviews were conducted with 14 participants, made up of doctors in oncology, physicians, surgeons, a cardiologist, an intensivist, a hematologist and a general practitioner. Interviews were recorded, transcribed and an inductive process was used for data analysis which allowed for categories to emerge from the data. Results: Eight themes emerged from the data analysis: improving the quality of life; palliative care as a role for oncologists; late referrals to palliative care, views on the World Health Organisation analgesic pain ladder; morphine a controversial means of pain control; team approach; family involvement and spiritual care. Conclusion: Palliative care was seen as an important intervention for a dying patient, but by introducing these services so late, patients are not benefitting from all that palliative care has to offer. Doctors did not always have a good understanding of when and how to provide palliative care. The following recommendations were made: (1) further research to be conducted in more private hospitals; (2)engage with management and doctors to begin the process of offering more formalised palliative care services at the hospital; (3) networking with available palliative care services, (4) organising palliative care training and workshops and (5) palliative care awareness campaigns.